On the Ampedini Gistel, 1848 (Coleoptera: Elateridae) of Central Asia, with a description of a new species of the genus Reitterelater Platia & Cate, 1990 - Prosvirov, Alexander S. (Zootaxa, 2017)
Some species of the Ampedini Gistel, 1848 of Central Asia are considered. A new species of the genus Reitterelater Platia & Cate, 1990 is described from Uzbekistan: R. kovalenkoi sp. nov. The systematic position of the little-known species Ampedus russicus Gurjeva, 1972 comb. rev. is discussed; notes on Reitterelater and allied genera are given.